Konsep Perlindungan Hukum Perbankan Nasional Dikaitkan dengan Kebijakan Kepemilikan Tunggal terhadap Kepemilikan Saham oleh Pihak Asing dalam Rangka Mencapai Tujuan Negara Kesejahteraan - Fontian Munzil; Sayid Mohammad Rifqi Noval (Fakultas Hukum Universitas Islam Indonesia, 2012)
This research analyzes whether the sole proprietorship policy can support national banking monitoring andhow this policy is implemented in the banking globalization, legal protection for national banking and concept of national banking development in globalization era in relation to the objectives of welfare state. The research uses normative juridical method with descriptive analysis. The findings are: first, the sole proprietorship policy does not apply to under 25% shareholding of a bank or share acquisitions in several banks. Second, the nature of sole proprietorship policy is futuristic, so it can reduce the discretion for national banking shareholding by foreign/global investors. Third, legal protections for national banking towards domination of national banking shareholding have been ineffective because the sole proprietorship policy only incorporates the same proprietorship of several banks. Fourth, in globalization era, the concept of national banking regulation independency for capital is adjusted to the business segment of each bank. In addition, an integrative monitoring should be applied to national banking activities, particularly to foreign parties who hold shares in several national banks without highly influenced by global banking regulation recommendation.